The Influence of Perception and Service on the Satisfaction Level of Pawn Gold Customers at the Handil Jaya Pegadaian Syariah Main Branch Office - Rohana; Rofiqoh Ferawati; Khusnul Istiqomah (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2022)
This study focuses on the perception and service of Sharia Pawnshops on the level of satisfaction of Sharia Pegadaian customers. Aims to find out how big the influence of perceptions and services on the level of customer satisfaction.(1) In this study, researchers used a sample of 100 people in the city of Jambi. Researchers with a questionnaire method filled out by each sample voluntarily. In this study, researchers used the SPSS version 16 application for windows 10. (2)The following results were obtained. There is a significant influence between the perception factor (X1) on the level of satisfaction (Y) of 18.5%. And the effect of service (X2) on the satisfaction level of 80.1%. The most influential factor on satisfaction is service. (3) Five factors that affect customer satisfaction, namely, product quality, service quality, emotional and price. Then it can be concluded that perceptions and services affect the satisfaction level of pawn gold customers at the main branch office of the Handil Jaya Pegadaian Syariah.